"The bad job brings the good one": photovoice study with female and male waste workers in Rwanda - Surchat, M.; Irakoze, M.; Kantengwa, S.; Konlambigue, M.; Spath, L.; Wilde, B.; Six, J.; Krutli, P.; Stauffacher, M. (Informa UK Limited, 2024)
Within the circular economy framework in Africa, sustainable waste management can contribute to improving the environment and creating green jobs. However, recycling activities are mostly carried out by informal workers, who are often forgotten in discussions about the circular economy. To ensure the development of a socially just circular economy, their voices must be heard and their needs accounted for. This study took place in Rwanda, a circular economy leader in Africa, and explored the experiences of workers engaged in biowaste recycling, with a particular focus on the distinctions between the experiences of female and male workers. We used photovoice as a methodology, allowing waste workers to visually report on the benefits and drawbacks of being involved in biowaste recycling. Seventeen waste recyclers took pictures representing different working experiences, which was followed by individual in-depth interviews to elicit the meaning behind each picture. Data analysis consisted of a reflexive thematic content analysis of interview transcripts and a participatory data analysis with the workers. The results show that the workers valued their jobs for their social relations at work, being responsible for a task, being productive, and generating savings. Workers negatively highlighted the health risks associated with waste sorting, difficult working conditions, and low salaries. We found gendered differences in workers’ marital status and access to paid work opportunities. Although working in waste recycling encompasses occupational risks, this photovoice study highlights that access to work improves workers’ relative well-being and that this type of circular economy can help create meaningful jobs.